TRANSFORMATION OF AFFIN COORDINATE SYSTEMS ON A PLANE. (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the theoretical foundations of affine coordinate system transformation. It analyzes the methods of converting coordinates from one affine system to another, the mathematical models of this process, and its practical applications. The study, based on geometry and linear algebra, also highlights the invariant properties of coordinate transformations.